(untitled) (Journal of history, 2019)
1989 was a turning point in a new history of Kazakhstan. One of the important events that did not receive enough attention from a scientific community was ethnic clashes in Novy Uzen (Mangyshlak region) that happened in June, 1989. The event was significant because it was initiated at the grass-root level, which was quite unusual for the totalitarian political system of the Soviet Union. In contrast to other scholars who viewed those clashes as solely interethnic conflict based on mistrust and ethnic hatred, the authors suggest approaching that conflict from the perspective of economic nationalism (Helleiner and Pickel 2005; Tsygankov 2005; Schulman 2000). The events in Novy Uzen were the first sign of the necessity to differentiate the needs of the national economic system and to transfer it under the control of the local Kazakh authorities. We can see the clashes in Novy Uzen as first seeds of emerging economic nationalism in Kazakhstan.